(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
Random high angle grain boundaries could be transformed into special, low energy boundaries (so called CSL boundaries), which affect the properties of materials. The formation of these special boundaries could be obtained through various combinations of thermal and mechanical treating. Changing the parameters of the treatments will strongly affects the quantity and quality of the special boundaries. Because of that it is essential to have a thorough knowledge and control over the conditions of the samples, such as the effective temperature and the strain field. Mapping these parameters could be accomplished by experimental and computational methods. In this paper the mapping of the effective temperature and the true strain field of a cylindrical pure copper sample via experimental and computational methods will be introduced. In addition it will be presented how the obtained data could be used in the further work.